(The possibility of using biologically extracted chemical compounds as anti-corona virus.). Issue 1 (April 2021) - Mahdi, Noor M.; Jawad, Ohood Salman
Abstract: Corona virus is a virus that has the ability to penetrate the wall of the inner epithelial lining of the lungs, and thus spread fear and panic in the hearts of ordinary people, as well as researchers. And once this virus began to be active in infecting people, starting with China and the rest of the world, scientists and researchers worked to search for appropriate treatment and appropriate prevention methods to get rid of the infection caused by this deadly virus. It is imperative to know a set of concepts related to this topic, including the most important general characteristics of the Coronavirus, as well as the structural structure and behavior of the host cell, including the cells of lung tissue in the human respiratory system. And how the virus affects cellular respiration, which leads to human death. Our current research deals with studying the possibility of using some naturally extracted chemical compounds as an anti-virus, specifically corona virus, based on the fixed proportions and quantities through which the mechanical effect of these compounds on Corona virus is observed, depending on previous studies in this field.